Annular ligament repair using allograft for the treatment of chronic radial head dislocation: a case report - Pari, Carlotta; Puzzo, Agnese; Paderni, Stefania; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2018)
Background: The annular ligament has a crucial role in the radial head stability and  it is critical to the proper functioning of the proximal  radio-capitellar joint. Its chronic injury may lead to radial head instability, elbow pain with decrease in motion and valgus deformity. Method: We present the case of a 53-year-old heavy laborer who reported a complex trauma of the right upper limb with a Floating Elbow Injury, associated to an open Monteggia fracture-dislocation. One month later, despite the definitive fixation with plates of  both the forearm and the supracondylar fractures, X-rays showed the persistence of the radial head dislocation. A triceps autograft reconstruction for treating the chronic radial head dislocation, as described in literature, was not indicated in our patient, due to the recent surgery at the distal humerus site. Thus, it was decided to proceed to allograft reconstruction using a peroneal tendon from a cadaveric donor, fixed by modified Bell-Tawse Technique. Results: Two years after the surgery, x-rays showed the complete fractures’ healing; however a radial head notching was found. Conclusions: Allograft reconstruction of the annular ligament deserves to be considered as an adequate technique, whenever the surrounding soft tissues are critically compromised. In literature, the radial head notching complication is reported to be up to 36 %, and it may be related to the surgical technique, regardless of the graft used.